2013
DOI: 10.1637/10496-011813-resnote.1
|View full text |Cite
|
Sign up to set email alerts
|

Relative Disease Susceptibility and Clostridial Toxin Antibody Responses in Three Commercial Broiler Lines Coinfected with Clostridium perfringens and Eimeria maxima Using an Experimental Model of Necrotic Enteritis

Abstract: Necrotic enteritis is an enteric disease of poultry resulting from infection by Clostridium perfringens with coinfection by Eimeria spp. constituting a major risk factor for disease pathogenesis. This study compared three commercial broiler chicken lines using an experimental model of necrotic enteritis. Day-old male Cobb, Ross, and Hubbard broilers were orally infected with viable C. perfringens and E. maxima and fed a high-protein diet to promote the development of experimental disease. Body weight loss, int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
30
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 30 publications
1
30
0
Order By: Relevance
“…They focus on the responses of the three breeds to necrotic enteritis. In general, they have found that Cobb are more susceptible to necrotic enteritis than Ross and Hubbard, exhibiting increased body weight loss and more severe intestinal lesions (52). Hubbard appear to have an intermediary susceptibility to necrotic enteritis with Ross emerging as the most resistant.…”
Section: Differences In Succession Between Breedsmentioning
confidence: 98%
“…They focus on the responses of the three breeds to necrotic enteritis. In general, they have found that Cobb are more susceptible to necrotic enteritis than Ross and Hubbard, exhibiting increased body weight loss and more severe intestinal lesions (52). Hubbard appear to have an intermediary susceptibility to necrotic enteritis with Ross emerging as the most resistant.…”
Section: Differences In Succession Between Breedsmentioning
confidence: 98%
“…To date, many studies have used RNA-seq 19 technology for transcriptome analysis in mammals. However, this is the first time this technology 20 has been used to study host pathogen interaction in NE in the intestinal mucosa using two inbred 21 White Leghorn chickens differing NE susceptibility. In this study, we experimentally induced NE 22 using E. maxima and C. perfringens to identify differentially expressed mRNA in intestinal mucosa 23 of the chicken lines 6.3 and 7.2 which have been selected for their disparate susceptibility to 24 Marek's Disease (Briles et al, 1977).…”
Section: Introductionmentioning
confidence: 99%
“…Hierarchical Table S4). 20 Third, we analysed RNA-seq data to identify immune-related genes, which are biologically 21 important for the host response to antigens. Based on the differences in genetic background 22 between line 6.3 and line 7.2, it was expected that some immune-related genes would be 23 differentially expressed between the two inbred lines that show different levels of NE 24 susceptibility.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This enteric infection is commonly well controlled by anticoccidials or antibiotic growth promoters, but the use of these compounds has been banned in animal feed in the European Union, and there is pressure to reduce their use worldwide because of the risk of multiple antimicrobial-resistant strains ( VAN IMMERSEEL et al, 2009). Thus, NE is re-emerging as an important disease in poultry, and there is concern about the increased risk of contamination of poultry products for human consumption, as C. perfringens is one of the most common causes of foodborne illness worldwide (NOWELL et al, 2010;CDC, 2012) Little is known about the susceptibility of poultry lines to NE; however, a recent study suggests that Cobb chickens are more susceptible to necrotic enteritis compared with Ross and Hubbard chickens (JANG et al, 2013). The disease occurs mostly in animals between 2-6 weeks of age and can vary from an acute to a subclinical form.…”
Section: Broiler Chickensmentioning
confidence: 99%